2016
DOI: 10.1002/mnfr.201500759
|View full text |Cite
|
Sign up to set email alerts
|

Glycative stress from advanced glycation end products (AGEs) and dicarbonyls: An emerging biological factor in cancer onset and progression

Abstract: In recent years, glycative stress from exogenous or endogenous advanced glycation end products (AGEs) and highly reactive dicarbonyls has gained great attention for its putative effects on cancer development. AGEs are a group of compounds formed from the complex chemical reaction of reducing sugars with compounds containing an amino group. AGEs bind to and activate the receptor for AGEs (RAGE), which is a predominant modulator of inflammation-associated cancer, and AGEs induce reactive oxygen species that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 180 publications
(314 reference statements)
0
67
0
Order By: Relevance
“…Oral administration of additional AGEs increased the CML level in sera, and this amount of AGEs did not generate overt toxicity to healthy mice but promoted the PCa development. Glycative stress from AGEs was concluded as a factor for cancer onset and progression, including PCa, and activation of the receptor for AGEs (RAGE)/sRAGE was considered the major molecular mechanism . Previous studies identified an increased expression of RAGE on both PCa cells and pro‐tumoral TAMs (in glioma) .…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of additional AGEs increased the CML level in sera, and this amount of AGEs did not generate overt toxicity to healthy mice but promoted the PCa development. Glycative stress from AGEs was concluded as a factor for cancer onset and progression, including PCa, and activation of the receptor for AGEs (RAGE)/sRAGE was considered the major molecular mechanism . Previous studies identified an increased expression of RAGE on both PCa cells and pro‐tumoral TAMs (in glioma) .…”
Section: Discussionmentioning
confidence: 99%
“…The binding of MGO and GLO1 is the reaction rate-determining step. Most studies of MGO in diabetes and cancer focus on GLO1 function [1,21]. The effect of MGO on GLO1 is two-pronged.…”
Section: Methylglyoxal Generation Metabolism and Damagementioning
confidence: 99%
“…Advanced glycation end products (AGEs) are generated by the non‐enzymatic reaction of sugars with proteins or lipids . They are produced in the body and in the process of preparing food .…”
Section: Introductionmentioning
confidence: 99%
“…Advanced glycation end products (AGEs) are generated by the non‐enzymatic reaction of sugars with proteins or lipids . They are produced in the body and in the process of preparing food . Aging, degenerative disorders, and in particular metabolic diseases including diabetes are associated with enhanced formation of AGEs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation